Analisis Yuridis Putusan Hakim Terhadap Tindak Pidana Penipuan (Studi Putusan Nomor : 70/Pid.B/2020/Pn.Bpd) - Z, Zulkifli; Mila, Tahjul; Y, Yusrizal (Jurnal Ilmu Hukum Reusam, 2021)
This study is to find out the proof of the crime of fraud and to find out the juridical analysis of the judge's decision on the crime of fraud in adjudicating the crime of fraud based on the decision Number: 70/Pid.B/2020/PN.Bpd. One of the laws that regulate social life is criminal law, which regulates all legal rules that determine what regulations against perpetrators of crimes should be imposed on perpetrators. Because basically the purpose of law is to uphold justice so that public order and peace can be realized. From the above description concerning acts or actions that violate the law and are not in accordance with the norms (laws) that have been established, it is a criminal act of fraud as regulated in Article 378 of the Criminal Code. As for this research, it is not an ordinary fraud but a fraud carried out by means of the position given to him so that it can be more burdensome for the perpetrators of criminal acts. In this decision, which is a decision on a criminal case of fraud, is it significant with article 378 of the Criminal Code. This research uses normative juridical research. The sources of legal materials used are primary legal materials and secondary legal materials and tertiary legal materials, and the technique of collecting legal materials in this study is a document or literature research technique (library research). The tool used to collect data in this research is a literature study, the data analysis used is by means of analysis of the interpretation method / legal interpretation in the form of systematic interpretation. Based on the results of the study, conclusions were obtained, namely: First, proof of criminal fraud against cases with Number 70/Pid.B/2020/PN.Bpd. it is in accordance with the formulation of Article 378 of the Criminal Code regarding fraud, through juridical considerations based on the factors revealed in the trial and the facts that are used as the basis for consideration to make a decision against the defendant. Second, in Decision Number: 70/Pid.B/2020/PN.Bpd. The Panel of Judges was not careful in using non-juridical legal considerations and in this case there should be a break in the new law because it was made based on it. In this decision the judge did not prioritize justice for the victim, indeed in the case of fraud there was no restitution for the victim, but at least the judge was more burdensome in punishment to the defendant by imposing a crime under Article 52 of the Criminal Code which explains that an official for committing a crime violates a special obligation from his position , or when he commits a crime, he uses the power, opportunity or means given to him because of his position, the punishment may be increased by one third.